Making Secure Land Tenure Count for Global Development Goals and National Policy Evidence from Zambia - Ali, Daniel Ayalew (World Bank E-Library Archive, 2019)
Adding a module designed to measure land tenure-related Sustainable Development Goals indicators to the 2018 round of Zambia's labor force survey shows low transferability and high levels of tenure insecurity. Having a title is associated with greater transferability and reduced insecurity. Although demand for titles, including willingness to pay, is high, current policies limit the scope for tenure regularization and reinforce rather than reduce gender discrimination. Efforts in this direction need to be preceded by (i) procedural reform to reduce costs, streamline procedures, and make them gender-sensitive; (ii) institutional change to increase the efficiency of service delivery and ensure record maintenance; and (iii) legal change to recognize customary tenure and improve land management and transferability. Adding the Sustainable Development Goals land tenure module to ongoing surveys has the potential to provide the evidence base needed to design results-based approaches for the land sector and reliably track progress